LANGUAGE AND CULTURE: AN ANALYSIS FROM THE PERSPECTIVE OF LINGUOCULTUROLOGY TEACHING - Mamatsoliyeva Sevinchoy Khamza kizi (TADQIQOTLAR, 2025)
Annotation: This article analyzes the relationship between language and culture from the perspective of linguoculturology. The science of linguoculturology studies the inextricable link between language and culture and aims to study the linguistic expression of national mentality, traditions and values. The article examines issues such as vocabulary, phraseological units, metaphors, translation problems, and changes in language and culture under the influence of globalization. This study highlights the place  of  linguoculturology  in  the  field  of  linguistics  and  education,  and  provides important  theoretical  and  practical  recommendations  for  language  learners  and translators.